Age modification of ozone associations with cardiovascular disease risk in adults: a potential role for soluble P-selectin and blood pressure - Day, Drew B.; Clyde, Merlise A.; Xiang, Jianbang; Li, Feng; Cui, Xiaoxing; Mo, Jinhan; Gong, Jicheng; Weschler, Charles J.; Zhang, Yinping; Zhang, Junfeng (Jim) (Journal of Thoracic Disease, 2018)
Background: Studies have suggested that age increases susceptibility to ozone-associated mortality, but the underlying mechanisms are unclear. In a previous study, personal exposure to ozone was significantly associated with a platelet activation biomarker, plasma soluble P-selectin (sCD62P), and blood pressure in 89 healthy adults, aged 22–52 years. The present study examines whether age modifies these associations in the same adults and in additional adults. Methods: Interaction terms of age and exposure were analyzed using hierarchical Bayesian mixed effects ridge regressions. Data from a similar additional study involving 71 healthy participants, aged 19-26 years, were pooled with the data from the first study to evaluate age effect modification when more young adults were added to the analysis. Results: In the 89 adults, significant age interactions were observed for past 24-hour and 2-week ozone exposures and sCD62P. Based on the pooled data (89 plus 71 adults), a 10 ppb increase in 24-hour ozone exposure was associated with increases in sCD62P and systolic blood pressure (SBP) by 22.3% (95% CI: 14.3%, 31.2%) and 1.35 (−0.18, 2.84) mmHg, respectively, at age 25; these values increased to 48.6% (32.7%, 65.1%) and 4.98 (2.56, 7.35) mmHg, respectively, at age 40. Conclusions: These results mechanistically suggest that increasing age enhances cardiovascular effects of ozone.